Physicochemical, antioxidant and microbial properties of fresh black stem sugarcane juice with addition of calamansi juice - Noor Afiqah Md Noor,; Maizura Murad,; Effarizah Mohd Esah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study was designed to determine the physicochemical, antioxidant and microbial properties of fresh sugarcane juice with calamansi juice addition. The sugarcane that was used in the experiments was the black cane variety (Saccharum officinarum). Sugarcane pressed with and without their peel was juiced and added with calamansi juice before analysis was carried out. Standard method was used to analyse physicochemical properties such as pH, total soluble solids, acidity and colour of sugarcane juice. Total phenolic content (TPC), DPPH and FRAP assay were conducted for antioxidant properties. Total plate count and yeast and mould count were carried out for the microbiological analyses. Two way analysis of variance (ANOVA) shows significant (p<0.05) difference on colour of sugarcane juiced after extraction with and without peel. There were no significant (p>0.05) difference shown for pH, acidity and total soluble solids of sugarcane juice pressed with and without peel. Sugarcane juice pressed with peel produced higher antioxidant value compared to sugarcane pressed without peel. However, sugarcane juice pressed without peeled showed a lower microbial count compared to sugarcane juice pressed with peel. The addition of calamansi juice proved to have significant (p<0.05) effect on colour, antioxidant and microbial count of the sugarcane juices.